The fierceness of fronted /s/: Linguistic rhematization through visual transformation - Calder, Jeremy (Language in Society, 2019)
This article explores the roles that language and the body play in the iconization of cross-modal personae (see Agha 2003, 2004). Focusing on a community of radical drag queens in San Francisco, I analyze the interplay of visual presentation and acoustic dimensions of /s/ in the construction of the fierce queen persona, which embodies an extreme, larger-than-life, and anti-normative type of femininity. Taking data from transformations—conversations during which queens visually transform from male-presenting into their feminine drag personae—I explore the effect of fluid visual presentation on linguistic production, and argue that changes in both the linguistic and visual streams increasingly invoke qualia (see Gal 2013; Harkness 2015) projecting ‘harshness’ and ‘sharpness’ in the construction of fierce femininity. I argue that personae like the fierce queen become iconized through rhematization (see Gal 2013), a process in which qualic congruences are construed and constructed across multiple semiotic modalities. (Iconization, rhematization, qualia, sociophonetics, gender, personae, drag queens)*
Disponible en ligne https://www-cambridge-org.proxy.bibliotheques.uqam.ca/core/journals/language-in-society/article/fierceness-of-fronted-s-linguistic-rhematization-through-visual-transformation/ADD4290AEAAA81B3474898265590BDD6
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; drag queen; identités LGBTQIA2+; lin2685; linguistique; premier cycle; queer; ressource en ligne; régions géographiques; san francisco; sciences humaines; thématiques; états-unis

Trans self-identification and the language of neoliberal selfhood: Agency, power, and the limits of monologic discourse - Zimman, Lal (International Journal of the Sociology of Language, 2019)
Sociocultural linguists share with transgender communities a strong interest in the power of individuals to assert agency over linguistic patterns. For trans people, a key principle of activism is gender self-determination, which treats each individual as the ultimate authority on their own gender identity. This article explores some of the ways gender self-determination and self-identification surface in transgender people’s linguistic practices. Three particular manifestations are highlighted: gendered identity labels, third person pronouns, and body part terminology. The observations offered on these subjects are based on a series of ethnographic projects carried out from 2006–2016 in transgender communities across several metropolitan areas in the United States and in online spaces frequented by trans people. However, the analysis goes beyond mere description by treating this kind of individualized linguistic agency as the product of cultural practice rather than an asocial given. Such a perspective introduces questions concerning why this form of agency arose in the time and place that it has. This article frames gender self-identification as an enactment of neoliberal personhood, in which individuals are framed as the driver of their destiny. What the ideology of neoliberal agency obscures, however, is that agency is not an equally distributed resource.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; agentivité; amériques; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; néolibéralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sofia; thématiques; transféminisme; états-unis